Somatic and visceral nervous systems - an ancient duality - Bertucci, Paola; Arendt, Detlev (BMC biology, 2013)
The vertebrate nervous system is deeply divided into ‘somatic’ and ‘visceral’ subsystems that respond to external and internal stimuli, respectively. Molecular characterization of neurons in different groups of mollusks by Nomaksteinsky and colleagues, published in this issue of BMC Biology, reveals that the viscero-somatic duality is evolutionarily ancient, predating Bilateria.
Gesehen am 12.05.2017